Bone marrow uptake of indolent non-Hodgkin lymphoma on PET/CT with histopathological correlation. Issue 10 (October 2015) - Lee, Elaine Yuen Phin; Gill, Harinder; Wang, Yong; Kwong, Yok-Lam; Khong, Pek-Lan
Abstract : Objective: To evaluate the diagnostic accuracy of PET/computed tomography (CT) in detecting marrow infiltration in indolent non-Hodgkin lymphoma (NHL) with histopathological correlation. Methods: All treatment-naive newly diagnosed indolent NHL with staging PET/CT were retrospectively evaluated for marrow infiltration and categorized on the basis of the PET/CT uptake pattern: normal (PET/CT negative), focal/diffuse (PET/CT positive). Bone marrow biopsy (BMB) was considered the standard, except in focal PET/CT uptake, which was confirmed to be positive or negative by serial PET/CT. The BMB pattern was assessed as diffuse and nondiffuse and the degree of lymphoid infiltration was documented. Results: Forty-six patients (mean age 59±15 years) were evaluated. In the PET/CT-positive group of 22 cases (diffuse=15, focal=7), BMB was positive in 21 cases. In 80% of diffuse PET/CT uptake cases, a diffuse BMB infiltrative pattern was observed. However, in cases with focal PET/CT uptake, no predominant histological pattern was observed. No correlation was found between semiquantitative uptake and degree of lymphoid infiltration on BMB ( r =0.2, P =0.434). In the PET/CT-negative group of 24 cases, 20 cases were BMB negative and four cases were positive. The overall diagnostic accuracy of PET/CT in determining marrow infiltration was 89% (sensitivity 84%, specificity 95%, positive predictive value 95% and negative predictive value 83%). Conclusion: PET/CT showed high specificity and positive predictive value with moderate accuracy in detecting marrow disease in indolent NHL. The metabolic uptake lacked a significant correlation with the degree of lymphoid infiltration, but a potential relationship may exist between the pattern of metabolic uptake and the BMB infiltrative pattern.